1997
DOI: 10.1128/aac.41.10.2274
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of ofloxacin isomers in the rat small intestine

Abstract: Ofloxacin, a chiral fluoroquinolone, possesses two optical isomers. The antibacterial activity of S-(-)-ofloxacin is 8 to 128 times higher than that of R-(+)-ofloxacin. In the rat, a saturable absorption process has been described for racemic ofloxacin. In the present study we investigated the mechanism underlying the in vivo intestinal absorption of ofloxacin enantiomers in the rat. Blood samples were collected from the portal vein. Our results show that the intestinal absorption of ofloxacin isomers is pH de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…At the same time, enantioselectivity of the two OFLX enantiomers during elimination was due to the differences in renal clearance. Rabbaa et al (1997) studied the removal mechanism of OFLX enantiomers in the rat intestine, and found that proteins affect the elimination kinetics of the two enantiomers. Our research established the pharmacokinetics of OFLX enantiomers in P. major, and found that they differed from those in humans and rats.…”
Section: Comparison Of Pharmacokinetic Parameters Between the Two Enamentioning
confidence: 99%
“…At the same time, enantioselectivity of the two OFLX enantiomers during elimination was due to the differences in renal clearance. Rabbaa et al (1997) studied the removal mechanism of OFLX enantiomers in the rat intestine, and found that proteins affect the elimination kinetics of the two enantiomers. Our research established the pharmacokinetics of OFLX enantiomers in P. major, and found that they differed from those in humans and rats.…”
Section: Comparison Of Pharmacokinetic Parameters Between the Two Enamentioning
confidence: 99%
“…Hence, special measures are undertaken to isolate individual enantiomers from these enantiomeric mixtures. Frequently, only one enantiomer is pharmaceutically active while the other may be toxic, ballast, or inactive . Therefore, to avoid the toxicities, side effects, and other problems, these antibacterial agents should be administered in the form of pharmaceutically active pure enantiomers.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, however, only bovine serum albumine protein [11,15] and cellulose tris (3,5-dimethylphenylcarbamate) [16] silica based columns have been employed for ofloxacin enantiomeric separation.…”
Section: Introductionmentioning
confidence: 99%